Simulation of upper-ocean biogeochemistry with a flexible-composition phytoplankton model: C, N and Si cycling and Fe limitation in the Southern Ocean - Mongin, Mathieu; Nelson, David M; Pondaven, Philippe; Tréguer, Paul (Deep Sea Research Part II: Topical Studies in Oceanography, 2006)
International audience We previously reported the application of an upper-ocean biogeochemical model in which the elemental composition of the phytoplankton is flexible and responds to changes in light and nutrient availability [Mongin, M., Nelson, D., Pondaven, P., Brzezinski, M., Tréguer, P., 2003. Simulation of upper-ocean biogeochemistry with a flexible-composition phytoplankton model: C, N and Si cycling in the western Sargasso Sea. Deep-Sea Research I 50, 1445-1480]. That model, applied in the western Sargasso Sea, considered the cycles of C, N and Si in the upper 400 m and limitation of phytoplankton growth by N, Si and light. We now report a new version of this model that includes Fe cycling and Fe limitation and its application in the Southern Ocean. The model includes two phytoplankton groups, diatoms and non-siliceous forms. Uptake of NO3− by phytoplankton is light dependent, but NH4+, Si(OH)4 and Fe uptake are not and can therefore continue through the night. The model tracks the resulting C/N and Fe/C ratios of both groups and Si/N ratio of diatoms, and permits uptake of C, N, Fe and Si to proceed independently when those ratios are close to those of nutrient-replete phytoplankton. When they indicate a deficiency cellular C, N, Fe or Si, uptake of the non-limiting elements is controlled by the content of the limiting element in accordance with the cell-quota formulation of [Droop, M., 1974. The nutrient status of algal cell in continuous culture. Journal of the Marine Biological Association of the United Kingdom 54, 825-855]. The model thus identifies the growth-limiting element and quantifies the degree of limitation from the elemental composition of the phytoplankton. We applied this model at the French KERFIX site in the Indian Ocean sector of the Southern Ocean, using meteorological forcing for that site from 1991 to 1995. As in the Sargasso Sea application, the flexible-composition structure provides simulations that are consistent with field data with only minimal tuning of model parameters. ...